Effectiveness of Sparcs on The Reading Comprehension Performance of Grade 6 Learners - Suplaag, Melbert Cagang; Sheena Atasha Rama PANTUJAN; Pauleen Kate Gimarino ROJAS; Julie Rose LAHOY; Anamie Dela Peña BAYER (RADINKA JAYA UTAMA PUBLISHER, 2025)
This study evaluated the effectiveness of the Sustainable Program for Accelerating Reading Comprehension Skills (SPARCS) in improving the reading comprehension performance of grade 6 learners at Poblacion, Liloan, Cebu. Using a true experimental research design, the study involved a control group and an experimental group, with pre-test and post-test assessments based on the PHIL-IRI reading comprehension tests. Findings indicate that before the intervention, both groups had similar reading comprehension levels, with most learners classified under the